2015
DOI: 10.1159/000382020
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cortical Thickness and Neurological Soft Signs in Patients with Chronic Schizophrenia and Healthy Controls

Abstract: Background: Neurological soft signs (NSS), i.e. subtle neurological abnormalities, have been frequently found in schizophrenia. Neuroimaging studies in schizophrenia have shown abnormal cortical thickness changes across the cortical mantle. However, few studies have examined relationships between NSS and cortical thickness abnormalities in schizophrenia. Method: A sample of 18 patients with chronic schizophrenia and 20 age-matched healthy controls were included. Cortical thickness was assessed on high-resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 53 publications
4
21
0
Order By: Relevance
“…Interestingly, this pattern of findings did not apply to the healthy controls (N = 20). In contrast, Kong et al [25] found negative correlations between NSS and cortical thickness in anterior cingulate, pericalcarine and superior/middle temporal regions in their healthy control group. In younger healthy subjects (mean age: 27-30 years), higher rates of NSS were associated with a reduction of right middle frontal gyrus, inferior frontal gyrus, middle and superior temporal gyrus and anterior cingulate gyrus [21,26].…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Interestingly, this pattern of findings did not apply to the healthy controls (N = 20). In contrast, Kong et al [25] found negative correlations between NSS and cortical thickness in anterior cingulate, pericalcarine and superior/middle temporal regions in their healthy control group. In younger healthy subjects (mean age: 27-30 years), higher rates of NSS were associated with a reduction of right middle frontal gyrus, inferior frontal gyrus, middle and superior temporal gyrus and anterior cingulate gyrus [21,26].…”
Section: Introductionmentioning
confidence: 76%
“…According to the literature NSS are structurally associated with morphological alterations of pre-and postcentral gyri, premotor area, cerebellum, middle and inferior frontal gyri, thalamus and basal ganglia, temporal and lingual gyri, inferior parietal lobule, insula, precuneus and occipital gyrus in younger patient samples [for review see : 11, 12]. In addition, in middleaged patients with chronic schizophrenia significant associations between NSS scores (Heidelberg Scale) and reduced cortical thickness in prefrontal, inferior temporal, superior parietal, postcentral and supramarginal cortices were demonstrated [25]. These findings parallel those of the present study and reflect the model of "cognitive dysmetria" developed by Andreasen et al [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…54 Significant cortical thinning has also been noted in this re gion in patients diagnosed with schizophrenia compared to matched controls. 55,56 Finally, 22q11 deletion syndrome and genetic risk for schizophrenia based on common gen etic variation have been associated with volumetric grey matter differences in the lingual gyrus and cuneus, as well as cortical thinning in the cuneus and pericalcarine and lingual gyri. 57,58 A recent paper examined LGI in medicated young adults who met the criteria for an atrisk mental state.…”
Section: Differences In Occipital Cortex Foldingmentioning
confidence: 99%
“…Neurological soft signs (NSSs) are subtle, non‐localizable neurological abnormalities in motor coordination, complex motor sequencing, sensory integration, and disinhibition (Chen et al, ; Heinrichs & Buchanan, ). NSSs have been frequently reported in patients with schizophrenia at different stages of the illness, including chronic schizophrenia, first‐episode schizophrenia, and in individuals with ultra‐high risk (UHR) for psychosis (Chan, Xu, Heinrichs, Yu, & Wang, ; Dazzan et al, ; Kong et al, ; Schröder et al, ). In addition, patients with schizophrenia and UHR individuals exhibit significantly higher NSS values compared with healthy controls, with UHR individuals situated intermediately between schizophrenia patients and controls (Chan, Xu, Heinrichs, Yu, & Gong, ; Chan, Xu, Heinrichs, Yu, & Wang, ).…”
mentioning
confidence: 99%